Financial Ratio Approach to Analyze Financial Performance: Comparison Before and After Merger - Dewi, Ghina Kemala; Basyir, Ashar (Journal of Business and Economics Research (JBE), 2025)
A merger is the process of combining two or more companies, where one company is maintained and the other is dissolved, with the assets of the dissolved company being transferred to the remaining company without liquidating it first. This study aims to determine the differences in financial performance at PT Bank CIMB Niaga Tbk before and after the merger by using a general financial analysis method, namely financial ratio analysis. The data used in this research is secondary data in the form of annual financial statements of PT Bank CIMB Niaga Tbk, taken from the period before the merger (2006-2007) and after the merger (2008, 2019, 2020). The type of data used in this study is quantitative research data. Quantitative data refers to data presented in the form of numbers that can be calculated with specific units. Financial performance is assessed using 4 indicators: Current Ratio, Debt to Equity, Net Profit Margin, and Total Asset Turnover. Based on the results of this study, it shows that from the four ratios calculated, two ratios had a positive change: the liquidity ratio measured using the Current Ratio and the profitability ratio measured using Net Profit Margin. There are two ratios that experienced negative changes after the merger: the solvency ratio measured using Debt to Equity Ratio and the activity ratio measured using Total Asset Turnover. The overall result from the calculations of these four ratios shows that there is a significant difference in financial performance before and after the merger. A limitation in this study is the ratio-based approach, where each financial ratio is measured individually. As a result, this study cannot be generalized to other studies.